2016
DOI: 10.1159/000443634
|View full text |Cite
|
Sign up to set email alerts
|

Creating Interactions between Tissue-Engineered Skeletal Muscle and the Peripheral Nervous System

Abstract: Effective models of mammalian tissues must allow and encourage physiologically (mimetic) correct interactions between co-cultured cell types in order to produce culture microenvironments as similar as possible to those that would normally occur in vivo. In the case of skeletal muscle, the development of such a culture model, integrating multiple relevant cell types within a biomimetic scaffold, would be of significant benefit for investigations into the development, functional performance, and pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…Previous animal studies showed that this AChR subunit transition occurs in the presence of motor axon endplates and confirmed that transcription of the epsilon gene (CHRNE) is stimulated by AChR Inducing Activity (ARIA) via ErbB receptors, a nerve derived ligand of the neuregulin-1 (NRG1) family (Martinou et al, 1991). Consistently, CHRNE transcripts are detected in rodent 2D and 3D skeletal muscle fiber cultures when co-cultured with nerve cells (Bach et al, 2003;Ostrovidov et al, 2017;Smith et al, 2016;Vilmont et al, 2016). However, despite significant progress toward directing human pluripotent stem cells (PSCs) to the motor neuron lineage Lippmann et al, 2014;Maury et al, 2015;Shimojo et al, 2015;Zhang et al, 2001) and establishing electrically and chemically responsive human muscle fibers in vitro (Madden et al, 2015), the first reports of human NMJ models -2D human muscle fiber and motor neuron co-cultures -were unable to demonstrate synapse maturation via the gamma to epsilon AChR subunit switch (Guo et al, 2011;Steinbeck et al, 2016), and there are no reports of epsilon AChR protein expression or function in culture in the absence of enforced gene expression.…”
Section: Introductionmentioning
confidence: 54%
“…Previous animal studies showed that this AChR subunit transition occurs in the presence of motor axon endplates and confirmed that transcription of the epsilon gene (CHRNE) is stimulated by AChR Inducing Activity (ARIA) via ErbB receptors, a nerve derived ligand of the neuregulin-1 (NRG1) family (Martinou et al, 1991). Consistently, CHRNE transcripts are detected in rodent 2D and 3D skeletal muscle fiber cultures when co-cultured with nerve cells (Bach et al, 2003;Ostrovidov et al, 2017;Smith et al, 2016;Vilmont et al, 2016). However, despite significant progress toward directing human pluripotent stem cells (PSCs) to the motor neuron lineage Lippmann et al, 2014;Maury et al, 2015;Shimojo et al, 2015;Zhang et al, 2001) and establishing electrically and chemically responsive human muscle fibers in vitro (Madden et al, 2015), the first reports of human NMJ models -2D human muscle fiber and motor neuron co-cultures -were unable to demonstrate synapse maturation via the gamma to epsilon AChR subunit switch (Guo et al, 2011;Steinbeck et al, 2016), and there are no reports of epsilon AChR protein expression or function in culture in the absence of enforced gene expression.…”
Section: Introductionmentioning
confidence: 54%
“…Such reductions were however not evident when cells were cultured on PA‐12 scaffolds, with comparable morphological and transcriptional phenotypes evident. This further outlines the applicability of this polymer and favorability of LS when fabricating scaffolds for musculoskeletal tissue engineering applications …”
Section: Discussionmentioning
confidence: 88%
“…Particularly when evaluating the specific AM process and polymer combination while creating physiologically representative in vitro models that are utilized within tissue engineering and or pharmaceutical screening applications. This research demonstrates cell type specific biocompatibility across a range of industry standard 3D printing techniques: SL, LS, and PolyJet, for incorporation within tissue engineering models of musculoskeletal and neurological disorders, in addition to pharmacological screening systems . In this work, we used C 2 C 12 , SH‐SY5Y, and HepG2 cell lines in order to ascertain critical evidence of cellular behavior in response to 3D‐printed candidate polymers due to their capacity to afford a range of optically transparent (Clear‐FL and VeroClear) and bioinert (PA‐12) parts from commercially available and accessible AM instrumentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between myogenic cells and non-myogenic cells in muscle tissue may influence myogenesis either by interacting directly or by secretion of paracrine factors (Figure 2). Motor neurons were used to form neuro-muscular junctions [49] and further adapted to a 3D culture system [50]. The presence of motor neurons had positive effects on myotube maturation [50].…”
Section: Co-culture Exosomes and Mirnamentioning
confidence: 99%